Knowledge, attitudes, beliefs and behaviours of older adults about pneumococcal immunization, a Public Health Agency of Canada/Canadian Institutes of Health Research Influenza Research Network (PCIRN) investigation - Schneeberg, Amy; Bettinger, Julie A; McNeil, Shelly; Ward, Brian J; Dionne, Marc; Cooper, Curtis; Coleman, Brenda; Loeb, Mark; Rubinstein, Ethan; McElhaney, Janet; Scheifele, David W; Halperin, Scott A (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Fewer Canadian seniors are vaccinated against pneumococcal disease than receive the influenza vaccine annually. Improved understanding of factors influencing pneumococcal vaccination among older adults is needed to improve vaccine uptake. Methods A self-administered survey measuring knowledge, attitudes, beliefs and behaviours about pneumococcal vaccination was administered to a cohort of seniors participating in a clinical trial of seasonal influenza vaccines at eight centers across Canada. Eligible participants were ambulatory adults 65 years of age or older, in good health or with stable health conditions, previously given influenza vaccine. The primary outcome was self-reported receipt of pneumococcal vaccination. Multi-variable logistic regression was used to determine factors significantly associated with pneumococcal vaccine receipt. Results A total of 863 participants completed questionnaires (response rate 92%); 58% indicated they had received the pneumococcal vaccine. Being offered the vaccine by a health care provider had the strongest relationship with vaccine receipt (AOR 23.4 (95% CI 13.4-40.7)). Other variables that remained significantly associated with vaccine receipt in the multivariable model included having heard of the vaccine (AOR 10.1(95% CI 4.7-21.7)), and strongly agreeing that it is important for adults > 65 to be vaccinated against pneumococcus (AOR 3.3 (95% CI 1.2-9.2)). Participants who were < 70 years of age were less likely to be vaccinated. Conclusions These results indicate healthcare recommendation significantly influenced vaccine uptake in this population of older adults. Measures to encourage healthcare providers to offer the vaccine may help increase coverage.